The Use of Mobile Apps for Islamic Learning: A Study on Accessibility and Learning Outcomes - Umar Ibrahim; Siddik Faruk Tilli (Saniya Institute, 2025)
The integration of mobile apps into Islamic education has the potential to enhance accessibility and improve learning outcomes. This study investigates the use of mobile apps for Islamic learning, focusing on their accessibility and impact on students' educational achievements. A mixed-methods approach was employed, involving surveys and interviews with students and educators from Islamic institutions. Data were analysed using statistical tests to assess the level of accessibility and the effectiveness of mobile apps in facilitating learning. The results indicated that a significant proportion of students found these apps easy to use, which correlated with improved learning outcomes, such as better memorization of Qur'anic verses and understanding of Hadith. However, some challenges, including limited access to quality content and digital literacy, were identified. The study concludes that while mobile apps are valuable tools for Islamic education, there is a need for ongoing enhancements to optimize their use. Recommendations are provided for app developers and educators to address these challenges and further integrate technology into Islamic learning.